Analisis Pengaruh Earning Per Share (EPS) dan Dividen Per Share (DPS) terhadap Harga Saham Pada PT. Elnusa Tbk - Erwinsyah Putra; Aris Munandar (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study aims to examine the effect of Earning Per Share (EPS) and Dividend Per Share (DPS) on Stock Prices at PT. Elnusa Tbk. This type of research includes associative research using secondary data obtained from financial reports on the idn financial.co.id website. The population in this study is the financial statements at PT. Elnusa Tbk for 15 years (2008-2021). The method used in selecting the sample was purposive sampling and determining the sample based on the criteria set by the researcher with a sample of 10 years (2012-2021). Based on the results of secondary data processing using the F test analysis method and t test, it is known that the variables Earning Per Share (EPS) and Dividend Per Share (DPS) simultaneously have no significant effect on stock prices. Partially, the results of this study indicate that the Earning Per Share (EPS) variable has no significant effect on stock prices, Dividend Per Share (DPS) has no significant effect on stock prices.